Imidazole propionate is a driver and therapeutic target in atherosclerosis - Mastrangelo, Annalaura; Robles-Vera, Iñaki; Mañanes, Diego; Galán, Miguel; Femenía-Muiña, Marcos; Redondo-Urzainqui, Ana; Barrero-Rodríguez, Rafael; Papaioannou, Eleftheria; Amores-Iniesta, Joaquín; Devesa, Ana; Lobo-González, Manuel; Carreras, Alba; et al. (Nature, 2025)
Atherosclerosis is the main underlying cause of cardiovascular diseases. Its prevention is based on the detection and treatment of traditional cardiovascular risk factors1. However, individuals at risk for early vascular disease often remain unidentified2. Recent research has identified new molecules in the pathophysiology of atherosclerosis3, highlighting the need for alternative disease biomarkers and therapeutic targets to improve early diagnosis and therapy efficacy. Here, we observed that imidazole propionate (ImP), produced by microorganisms, is associated with the extent of atherosclerosis in mice and in two independent human cohorts. Furthermore, ImP administration to atherosclerosis-prone mice fed with chow diet was sufficient to induce atherosclerosis without altering the lipid profile, and was linked to activation of both systemic and local innate and adaptive immunity and inflammation. Specifically, we found that ImP caused atherosclerosis through the imidazoline-1 receptor (I1R, also known as nischarin) in myeloid cells. Blocking this ImP-I1R axis inhibited the development of atherosclerosis induced by ImP or high-cholesterol diet in mice. Identification of the strong association of ImP with active atherosclerosis and the contribution of the ImP-I1R axis to disease progression opens new avenues for improving the early diagnosis and personalized therapy of atherosclerosis.
Online veröffentlicht: 16. Juli 2025
Gesehen am 15.09.2025